The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1159/000246547
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid Antibodies and Anetoderma: Are They Associated?

Abstract: Background: Macular atrophy or anetoderma is a rare skin disease of unknown pathogenesis, characterised by wrinkled or flaccid skin. Objective: The finding of anetoderma in 5 patients followed up because of false-positive seroreactions of syphilis prompted us to study the occurrence of antiphospholipid (aPL) antibodies in anetoderma. Methods: 14 unselected patients with primary anetoderma (PA) were collected from hospital records and clinical, immunological and histological findings were compared in the two pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 11 publications
0
51
0
Order By: Relevance
“…Antiphospholipid antibodies have been reported to associate with several cutaneous diseases in which vascular abnormalities seem to play a major part. Recently, nonvascular, cutaneous diseases including melanoma and anetoderma have been reported in patients with antiphospholipid antibodies [6, 7, 8]. To our knowledge, these are the first reported cases of subcutaneous GP associated with antiphospholipid antibodies.…”
Section: Discussionmentioning
confidence: 96%
“…Antiphospholipid antibodies have been reported to associate with several cutaneous diseases in which vascular abnormalities seem to play a major part. Recently, nonvascular, cutaneous diseases including melanoma and anetoderma have been reported in patients with antiphospholipid antibodies [6, 7, 8]. To our knowledge, these are the first reported cases of subcutaneous GP associated with antiphospholipid antibodies.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies reveal that this skin disorder is more frequent in patients with lupus erythematosus who have these antibodies than in patients with lupus erythematosus lacking them [10, 11, 12, 13]. This fact suggests a closer relationship of anetoderma with antiphospholipid antibodies and antiphospholipid syndrome than with lupus erythematosus itself.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, the literature contains reports of 35 PA patients demonstrated to have aPL, whether as an isolated laboratory finding (LAC and/or aCL, and/or aβ2GPI), as part of APS, or in conjunction with other clinical and/or laboratory signs of autoimmunity, including SLE. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. The rapid growth in the number of descriptions of such patients in the literature, from 13 patients until 2000 [26][27][28][29][30][31] to almost double since then, i.e., 22 patients [32][33][34][35][36][37][38][39][40][41], is a reflection of the increased awareness of this association among clinicians.…”
Section: Association With Aplmentioning
confidence: 99%
“…Stephansson et al were the first to demonstrate that patients with aPL with or without SLE, are prone to develop PA [27,29]. In 1991, they found that 5 out of 33 patients with SLE and positive LAC had PA, whereas among 37 SLE patients who were LAC-negative, none had PA [27].…”
Section: Association With Aplmentioning
confidence: 99%
See 1 more Smart Citation